Short Communication: Herpetofauna diversity, potential ecotourism in Mount Galunggung, West Java, Indonesia - AWAL RIYANTO; TAUFAN NURZAMAN SULAEMAN; NUR RACHMAN; DIKI MUHAMAD CHAIDIR; WAHYU TRILAKSONO; ACHMAD FARAJALLAH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Riyanto A, Sulaeman TN, Rachman N, Chaidir DM, Trilaksono W, Farajallah A. 2019. Short Communication: Herpetofauna diversity, potential ecotourism in Mount Galunggung, West Java, Indonesia. Biodiversitas 20: 1173-1179. Here we provide a list of herpetofauna at Mount Galunggung, West Java, Indonesia as potential biodiversity for ecotourism. Data were collected from our observations in March 2013 and November 2018 using visual and acoustic encounter search methods in the three zones  (hot springs, craters, and foothills) on the nature tourism destination of the mount. We revealed 35 species of herpetofauna and their local distribution on these zones. Even though the diversity of herpetofauna has not been observed completely, we suggested that the biodiversity data from this zone should be used as the basic capital in turning nature tourism base into ecotourism base, so that it would provide more benefits to biodiversity conservation itself and to the local community.